Les territoires du tramway moderne : de la ligne à la ville durable - Jacques Stambouli (Développement Durable et Territoires)
How can new tramways lines promote the development of sustainable cities? This article attempts to address this question through the use of a theoretical model, which situates the economic transport system within three contexts: the larger economic environment, the social environment and the natural environment. A new tramway line constitutes a new supply within the economic transport system of an urban area and this supply in turn produces potential effects within that system and its three environments. These effects, which are identified on the basis of studies carried out by urban planning agencies in Nantes, Grenoble and Strasbourg, are grouped together in three geometrical configurations: the line, the corridor, and the perimeter. These forms can then be organized into concrete territories such as the street, the pedestrian neighborhood and the city. The sustainable city project can thus use the potential effects of modern tramways for the simultaneous reproduction of the economic sphere, the social sphere and the biosphere within the urban space.